NEW DATA ON QUASI-PERIODICAL REGULARITIES IN ACTIVATION OF FRACTURES IN REAL TIME BASED ON MONITORING OF MAGNITUDES OF SEISMIC EVENTS: CASE STUDY OF THE BAIKAL RIFT SYSTEM - Sherman S.I.; Savitsky V.A. (My University, 2006)
An algorithm for researching a quantitative index of seismic activity (QISA) of faults. The index provided a ranking of the faults by degrees of their recent activity on the real time scale and enabled analyses of contributions of faults varying in ranks in the seismic process. Being represented numerically, the index made it possible to unambiguously distinguish active, low-active, and inactive faults within the recent geological development stage.